Exploring Chemokine Homodimer Stability: Structural Insights into CXC and CC Interfaces - David Budean; Yasser Almeida-Hernández; Jitendra Pandey; Joel Mieres Pérez; Elsa Sánchez García; Ellinor Haglund (Biophysica, 2024)
Chemokine ligands play a pivotal role in immune response by mediating cell migration and coordinating cellular processes through interactions with chemokine receptors. Understanding their sequence and structural integrity is crucial for elucidating their biological functions and potential therapeutic applications. In this study, we investigate the dimer interface between two distinct homodimer topologies: CXC and CC homodimers. Despite nearly identical monomeric structures, the rigid CXC interface is characterized by interactions between the N-loop/β-sheet regions, while the more flexible CC interface involves interactions through the unstructured N-terminal regions. Our structural and biophysical analyses indicate no significant differences in the free energy of folding (2–8 kcal/mol) and binding (10–14 kcal/mol) between the two homodimer topologies, showing that their free energy is primarily driven by sequence. We hypothesize that the biological signal is driven by the malleability of the dimer, depending on the binding interface. Understanding these structural dynamics opens new possibilities for designing chemokine-based therapeutics to modulate immune responses in diseases such as cancer, inflammation, and autoimmune disorders.